Puberty Education from The Side of Science and Religion: Urgency of The Post-Milenial Era - Anis Trianawati; Yuswa Istikomayanti; Truli Maulida (Tarbiyah : Jurnal Ilmiah Kependidikan, 2020)
To develop an integrated puberty education design in terms of science and religion, this development research was carried out using the 4D method (Define, Design, Develop, Disseminate). The results of the design and development stages were implemented at MTs Muhammadiyah 1 Malang, East Java. These parameters include aspects of student self-awareness, student self-identity. The aspects of students' self-awareness and self-identity obtained a gain score with medium and low levels. This is a challenge for teachers and parents in facing the digital era and the post-millennial generation with such a large flow of information. The urgency of developing puberty education is discussed further in this article.